Algeria's exploitation of solar energy as a gateway to integration into global value chains (Journal of Economic Additions, 2026)
The main aim of this study is to identify Algeria's solar energy potential, and assess its capacity to integrate into global value chains. It also intends to shed light on Algeria's position in global value chains as a clean and eco-friendly energy source, making it vital for achieving sustainable development and energy transition. Despite Algeria's vast solar potential, underutilization persists, hindering strategic export objectives. Success requires a firm institutional commitment and the localization of advanced technologies through international collaboration and scientific exchange. Moreover, attracting foreign investment is vital to bridge the gap between resource availability and large-scale renewable energy exploitationJel Classification Codes: F23.Q42
Keywords: Renewable Energies. traditional energies.Solar energy. Electric power production. Global value chains